2010
DOI: 10.1186/1471-244x-10-38
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of fish, omega-3, omega-6 polyunsaturated fatty acids and vitamin D and the prevalence of psychotic-like symptoms in a cohort of 33 000 women from the general population

Abstract: BackgroundLow intake of fish, polyunsaturated fatty acids (PUFA) and vitamin D deficiency has been suggested to play a role in the development of schizophrenia. Our aim was to evaluate the association between the intake of different fish species, PUFA and vitamin D and the prevalence of psychotic-like symptoms in a population-based study among Swedish women.MethodsDietary intake was estimated using a food frequency questionnaire among 33 623 women aged 30-49 years at enrolment (1991/92). Information on psychot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 59 publications
2
62
0
3
Order By: Relevance
“…A large epidemiologic investigation of over 33 000 women concluded that high intake of omega-3 fatty acids during pregnancy decreases the incidence of schizophrenia in the offspring 117 . In vitro,…”
Section: Polyunsaturatd Omega-3 Fatty Acids Modulate Cmementioning
confidence: 99%
“…A large epidemiologic investigation of over 33 000 women concluded that high intake of omega-3 fatty acids during pregnancy decreases the incidence of schizophrenia in the offspring 117 . In vitro,…”
Section: Polyunsaturatd Omega-3 Fatty Acids Modulate Cmementioning
confidence: 99%
“…El EPA desempeña un papel cardioprotector en el cuerpo humano, mientras que el DHA interviene en el desarrollo de tejidos nerviosos, particularmente cerebro y retina (Valenzuela & Videla, 2011). El consumo humano de estos AG aporta beneficios para la salud pues previenen el desarrollo de múltiples patologías, entre las que destaca la enfermedad cardiovascular y eventos coronarios (Brookhyser, 2006; Kris-Etherton, Harris, Lawrence & Nutrition Comittee, 2002;Vrablík, Prusíková, Snejdrlová & Zlatohlávek, 2009); también existe evidencia clínica de su participación benéfica en enfermedades con inflamación crónica (University of Maryland, 2011;Wall, Ross, Fitzgerald & Stanton, 2010); se ha encontrado asociación entre su consumo y la disminución en la aparición de depresión y desórdenes mentales (Hedelin et al, 2010;Sánchez-Villegas, Henríquez, Figueiras, Ortuño, Lahortiga & Martínez-González, 2007), además de que se sugiere que protegen contra lesiones cardiacas y hepáticas asociadas a isquemia (Valenzuela et al, 2011).Al considerar dichos beneficios, las recomendaciones actuales sobre su consumo dadas por la Asociación Americana del Corazón (American Heart Association), sugieren incluir pescado en la dieta cuando menos dos veces por semana (Gidding et al, 2009;Kris-Etherton et al, 2002;Lichtenstein et al, 2006). Los estudios sobre la composición nutrimental de especies marinas de consumo humano permiten conocer las propiedades alimenticias de los peces, y generan información útil para fines terapéuticos y nutricionales (D'Armas, Yáñez, Reyes & Salazar, 2010).…”
unclassified
“…The researchers found that, in 45 to 70 year-old people, the increase omega-3 of sea origin (EPA -Eicosapentaenoic Acid Consumption and DHA -Docosahexaenoic Acid) consumption was associated with reduction in the risk of cognitive function loss (19%). Hedelin et al 38 also found that the risk of psychotic symptoms was 53% lower in women who consumed fish 3-4 times/week when compared to the ones who hardly consumed it.…”
Section: Kalmijn Et Almentioning
confidence: 97%